Bio-reduction of free and laden perchlorate by the pure and mixed perchlorate reducing bacteria: Considering the pH and coexisting nitrate. (August 2018) - Shang, Yanan; Wang, Ziyang; Xu, Xing; Gao, Baoyu; Ren, Zhongfei
Abstract: Pure bacteria cell ( Azospira sp. KJ ) and mixed perchlorate reducing bacteria (MPRB) were employed for decomposing the free perchlorate in water as well as the laden perchlorate on surface of quaternary ammonium wheat residuals (QAWR). Results indicated that perchlorate was decomposed by the Azospira sp. KJ prior to nitrate while MPRB was just the reverse. Bio-reduction of laden perchlorate by Azospira sp. KJ was optimal at pH 8.0. In contrast, bio-reduction of laden perchlorate by MPRB was optimal at pH 7.0. Generally, the rate of perchlorate reduction was controlled by the enzyme activity of PRB. In addition, perchlorate recovery (26.0 mg/g) onto bio-regenerated QAWR by MPRB was observed with a small decrease as compared with that (31.1 mg/g) by Azospira sp. KJ at first 48 h. Basically, this study is expected to offer some different ideas on bio-regeneration of perchlorate-saturated adsorbents using biological process, which may provide the economically alternative to conventional methods. Graphical abstract: Image 1 Highlights: A novel biosorbent originated from wheat residuals was prepared for ClO4 − uptake. Bio-reduction of free and laden perchlorate was conducted by microorganism. Pure and mixed microorganisms were employed for the bio-reduction process. Effect of coexisting laden nitrate on reduction of laden perchlorate was evaluated.